Bone evaluation of dental implants: Linear distances measured through cone beam computed tomography (Research, Society and Development, 2024)
The aim of this study was to evaluate by means of cone beam computed tomography (CBCT), the relationship of dental implants with the noble structures. The peri-implant bone “volume” in vertical and horizontal linear measurements in the maxilla and mandible, the peri-implant linear measurements in the cervical, middle and apical thirds and the peri-implant linear bone measurements in the buccal and lingual surfaces. Using the i-CAT Vision program, 66 perimplant regions were evaluated in 24 patients in a private dental radiology service. Parasagittal images with 1:1 mm were used in the distance measurements between implants and noble structures and measures of the buccal and lingual bone volume at cervical, middle and apical thirds. The mandible showed a significant difference in the pattern established in the literature compared with the maxilla in relation to the distance of implants to the noble structures (p ≤ 0.05). The mandible showed significant difference concerning to a higher perimplant bone volume compared to the maxilla (p ≤ 0.05). The middle and apical thirds of the implants showed a higher percentage of perimplant bone volume with 59.1% (average third) and 74.2% (apical), whereas the buccal implants had the highest percentage out of the standard (78.8%). It was concluded that the distance of dental implants to noble structures proposed in the literature was respected in most assessments performed, maxilla showed low amount of perimplant bone tissue compared with the mandible; the cervical third of dental implants tested showed fewer perimplant bone tissue and buccal faces showed lower amount of bone tissue than the lingual faces.